Sex differences in influenza vaccine-induced immunity and protection in mice with obesity - Wolfe, Brian William (My University, 2025)
Host-associated factors, including biological sex (i.e., male or female as determined by chromosomes, gonads, and sex steroids) and obesity, impact immune responses to influenza vaccines. Whether or not obesity impacts influenza virus vaccine responses in a sex-specific manner is not known. Our objectives were to investigate sex differences in influenza vaccine-induced immunity and protection in a mouse model of diet-induced obesity (DIO). Five- to six-week-old male and female C57BL/6 mice were randomly assigned to either a high-fat diet (HFD, 60kcal% fat) or a low-fat diet (LFD, 10kcal% fat), and body mass was recorded weekly. Mice on HFD with body mass ≥20% than the average body mass of age- and sex-matched mice on the control diet were considered obese. Obese and non-obese male and female mice, obtained after a diet treatment for 12 weeks, were vaccinated with the mouse-adapted inactivated A/California/04/2009 H1N1 (ma2009 H1N1) vaccine (20µg in 40µL phosphate buffered saline) and boosted after 21 days post-vaccination (dpv). At 35 dpv, plasma samples were collected to measure antibody responses by enzyme-linked immunosorbent assay (ELISA) and virus-neutralizing assays. Subsets of mice were euthanized at 35 dpv to quantify B and T cell responses in the spleen and bone marrow by flow cytometry. At 42 dpv, vaccinated mice were challenged intranasally with 5 log10 TCID50 of the mouse-adapted A/California/04/2009 H1N1 drift variant virus (i.e., ma2009 H1N1dv) (in 30µL of Dulbecco’s Modified Eagle Medium). Body mass was recorded daily for 21 days post-challenge (dpc) to determine disease severity and protection. Another subset of mice was euthanized at 3 dpc to collect lung samples for measuring replicating virus titers and assessing inflammatory changes. After 12 weeks of diet treatment, 100% of the male and 67% of the female mice became obese. Males and females with obesity had significantly greater body mass, glucose intolerance, and body mass index than the non-obese controls (p<0.05 in each case). At 35 dpv, IgG, IgG2c, and virus-neutralizing antibody (nAb) titers were higher in females than in male mice, irrespective of obesity. Importantly, males with obesity had the lowest levels of IgG, IgG2c, and nAb titers compared with the other groups. After the virus challenge, a change in body mass was compared for 21 dpc. In agreement with the lowest levels of antibodies, vaccinated obese males were least protected, as evidenced by higher absolute (i.e., in gm) and relative (i.e., percentage change from the baseline) body mass loss. Similarly, both obese and non-obese females had higher antibody titers than males, which allowed them to more effectively clear replicating virus from the lungs within 3 dpc. While 75% (i.e., 3/4) of the vaccinated non-obese males were able to clear, none of the vaccinated obese males (i.e., 4/4) could clear replicating viruses from the lungs. Vaccinated obese males also had higher inflammatory cytokines and chemokines in the lungs and suffered with greater pulmonary inflammatory changes in histopathology analysis. Despite the lower effectiveness of the influenza vaccine in males with obesity, vaccination still significantly reduced virus replication in the lungs and lowered inflammatory cytokines such as IL-6 compared to the unvaccinated mice, indicating the benefit of getting vaccinated for all groups, including the obese males. Flow cytometry analysis of splenic cells at 35 dpv showed similar frequencies of B cells, including plasmablasts, plasma cells, and memory B cells, as well as T helper and T follicular helper (Tfh) cells in the spleen. However, in the bone marrow, the frequencies of plasma cells at 35 dpv were higher in female mice compared to males, irrespective of obesity. Our data illustrate that biological sex differences to inactivated influenza vaccine-induced immunity and protection are observed even in mice with obesity. We also observe that the antibody production after influenza vaccination is inferior in males with obesity, and they are less protected from subsequent influenza virus challenge. This is likely mediated by the inefficiency of B cells to produce antibodies in obese males, which warrants further investigation. These data highlight the need of consideration of the interaction of biological sex and obesity during the design and testing of influenza vaccines in animal and human models.
Keywords: Influenza; Vaccination; B cell response; Obesity; Sex differences